Effect of probiotic bacteria in composition of children's saliva. (February 2019) - Sarmento, Érika Gomes; Cesar, Dionéia Evangelista; Martins, Maurilio Lopes; de Oliveira Góis, Elton Geraldo; Furtado Martins, Eliane Mauricio; da Rocha Campos, André Narvaes; Del'Duca, Alessandro; de Oliveira Martins, Aurélia Dornelas
Abstract: Probiotics are widely used in the food industry and may affect the oral microbiota. This study aimed to evaluate the effect of petit-suisse plus probiotic on the microbiota of children's saliva. Strawberry flavor petit-suisse cheese plus green banana flour without Lactobacillus casei (control) and with addition of Lactobacillus casei (probiotic) were prepared and used in the experiments. The feasibility of adding probiotic to petit-suisse was assessed over 28 days. Saliva samples from volunteers who consumed the petit-suisses produced were collected before the period of consumption of the products (T0), on the last day of consumption of petit-suisse (T1) and two weeks after the consumption stopped (T2 - post treatment). The samples were immediately fixed with paraformaldehyde in a final concentration of 2%, after which the bacteria of interest were identified by Fluorescent In Situ Hybridization (FISH) and counted with the aid of an epifluorescence microscope. Lactic bacteria were viable between 10 8 and 10 9 CFU·g −1 for 28 days of storage at 4 °C. Both products (control and with L. casei added) were able to significantly reduce (p < 0.05) the total number of microorganisms and Streptococcus mutans in the volunteers' saliva. However, only the product plus L. casei decreased density of Agreggatibacter actinomycetemcomitans, as well as being able to maintain the low density of Porphyromonas gingivalis post treatment. Therefore, the petit-suisse cheese developed showed the ability to carry probiotic microorganism, being a potential alternative for reducing potentially pathogenic microbiota in the oral cavity. Highlights: Petit-suisse cheese with L. casei presented satisfactory microbiological quality, being a potentially probiotic product. The product with added L. casei was shown to be able to reduce A. Actinomycetemcomitans and S. mutans . Probiotic petit-suisse had beneficial effects on the oral health of the children.